A Semiotic Approach to Information in Economics - Herrmann-Pillath, Carsten (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2020)
Information is central to modern economics, but mostly treated in a disembodied form. The paper suggests a semiotic approach to information that interprets information in terms of thermodynamic information theory. This builds on C. S. Peirce’s concept of finality, relating final causes to energetic transformations in the economy, which operate in the efficient-causal mode. I substantiate this argument in a semiotic analysis of design as mediating such transformations via technology.